Demitologi Bultmann Ditinjau Dari Sudut Pandang Teologis Antropologis dan Peran Pendidikan Agama Kristen - Rivosa Santosa (PT FORMOSA CENDEKIA GLOBAL, 2023)
Demythologization is a method that was born by Bultmann with the aim of making it easier for humans to understand God. Discussing supernatural events and the story of Jesus' life which are considered myths results in damage to the foundation of Christian faith in terms of the inerrancy of the Bible and the figure of Jesus as the Savior who redeems human sins. Bultmann uses an anthropological point of view in his demythological process. When man speaks of God, man speaks of himself. And when humans talk about themselves, if they are not based on the word of God, then humans align with the existence of God which is spoken of as humans. Through qualitative methods by collecting literature study data, human beings are described from an anthropological point of view from their spiritual and rational dimensions. Likewise, the role of Christian Religious Education (PAK) encourages people to understand themselves through learning resources and ways of learning that are based on the Bible which is the word of God.